Insect pests and diseases in Indonesian forest: an assessment of the major threats, research efforts and literature - Nair, K.S.S. (Center for International Forestry Research, 2000)
To understand the potential role of forest products in household livelihoods, a study of the woodcraft industry in Zimbabwe was initiated. The woodcraft industry has increased steadily since the late 1980s. The factors driving the upsurge in the woodcraft industry are: (1) the increased demand by tourists; and (2) the need by rural households to find cash income sources. The structural adjustment programme, with one of its emphases being the decontrol of the currency, has probably played a key role in driving the rise in woodcraft production. Although all markets have a committee and all have some basic rules governing their operations, few rules are strictly enforced. There is also a lack of enforcement of the national legislation that governs the use of the tree resources. The local traditional rules governing resource use from the commons are also not strong. Given the problems in the national legislation and in the local rules, it is difficult to see how the resource can be managed on a sustainable basis. It appears that the benefits from the industry may not be substantial given the lack of interest in the market from outsiders, and the various elites who could monopolise the trade due to the lack of enforcement structures in place. In communal areas, where deforestation is advanced, the selective use of certain species for carving is likely to drive the species to local extinction. The carvers are likely to switch to different tree species to maintain their production levels. Major pests and diseases of natural and planted Indonesian forests have been reviewed, threats assessed and a bibliography compiled. Indonesia has about 96 million ha of natural forests, dominated by dipterocarps, and 4 million ha of forest plantations, About half the plantations are in Java, consisting of long-established species eg., Tectona grandis, and half in Sumatra and Kalimantan, mainly fast growing pulpwood species. Major plantation species include Tectona grandis, Pinus merkusii, Acacia mangium, etc. Only small-scale plantations exist for the other species reviewed e.g., Alstonia spp., Anthocephalus sp., etc. Occasional and unpredictable insect outbreaks have occurred in natural stands of, Plaquium sp, mangroves, etc., but plantations of teak, pine, mahogany and Paraserianthes falcatoria etc., are damaged by pests every year. In natural forests high host density appears to be a predisposing factor for pest build-up. Serious pests occur on Tectona grandis, Pinus merkusii, falcatoria and Swietenia macrophylla, with the most damaging being the Paraserianthes trunk borer, Xystrocera festiva. Disease problems are less significant than pests in the natural forests and no major disease outbreak has occurred in plantations, although many fungal diseases are prevalent in nurseries. No major pest or disease has been recorded on the minor plantation species, but their history is too short and planted areas too small to draw reliable conclusions on their susceptibility. There are indications of impending problems eg., root rot in Eucalyptus spp. and root and stem rot in Acacia mangium. There is also the risk of new pests in Acacia mangium, Gmelina arborea, Shorea spp. and Peronema sp. Research capacity in Indonesia is inadequate to meet the existing and future challenges and more collaboration between Government, universities and plantation companies is needed for pest and disease surveillance and research in the rapidly expanding forest plantations.